Measure order of convergence without an exact solution, Euler vs Milstein scheme - Schmitz Abe, K; Shaw, W (2005)
The purpose of this paper is to measure the strong and weak order of convergence of both the Euler and Milstein schemes using a stochastic volatility model and an N−dimensional Exponential Brownian Motion Process (EBM). An exact solution is normally required to calculate the order of convergence, however there are none available for this volatility process. We propose a method to solve this problem. We also show numerically that when we apply the Milstein scheme to an N−dimensional stochastic process, there is a need to take into account the correlation between the systems.